2018
DOI: 10.1073/pnas.1715227115
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus generalization as a mechanism for learning to trust

Abstract: SignificanceHumans can learn to trust through direct social experiences. In our everyday lives, however, we constantly meet new people where judgments of trustworthiness are blind to reputation. In these cases, what drives decisions to trust? We find a simple learning mechanism observed across species—stimulus generalization—is deployed in complex social learning environments: Individuals distrust strangers who implicitly resemble those known to be untrustworthy. These behavioral findings were mirrored at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 50 publications
3
80
1
Order By: Relevance
“…During the test, the intensity of the light was gradually modified, and the animals’ rewarded response gradually increased with the similarity between the test light and the learning light. In a more recent study in humans (FeldmanHall et al, ), a similar generalization gradient of appetitive responses was found. Thus, participants preferred to play (prosocial behavior) with individuals who resembled an individual previously experienced as trustworthy.…”
Section: Introductionsupporting
confidence: 65%
“…During the test, the intensity of the light was gradually modified, and the animals’ rewarded response gradually increased with the similarity between the test light and the learning light. In a more recent study in humans (FeldmanHall et al, ), a similar generalization gradient of appetitive responses was found. Thus, participants preferred to play (prosocial behavior) with individuals who resembled an individual previously experienced as trustworthy.…”
Section: Introductionsupporting
confidence: 65%
“…People are able to form trustworthiness judgments quickly from someone's appearance with high reliability across individuals (Engell et al, 2007;Todorov et al, 2013;FeldmanHall et al, 2018). In the present study, despite variability in perceptions of neighborhood disorder, there was no difference in the ability to label a face as trustworthy or untrustworthy compared to the original ratings based on the Todorov and colleagues computer-generated faces (Oosterhof and Todorov, 2008).…”
Section: Discussioncontrasting
confidence: 52%
“…The stimulus generalization and stimulus RT findings suggest that 5-HTT -/rats may respond gradually more trustworthy to the stimuli, to finally categorize the ambiguous stimuli in the same way as 5-HTT +/+ did. The initial less trustworthy response to the ambiguous stimuli in 5-HTT -/rats may reflect an aversive emotion (FeldmanHall et al 2018) , in line with the anxious phenotype of these animals (Olivier et al 2008) . However, the 5-HTT +/+ rats behaved in the opposite way and gradually responded less trustworthy (or more suspicious) to the stimuli.…”
Section: Discussionmentioning
confidence: 81%
“…This type of decision-making is much related to emotion, not only in humans (Rustichini 2005) but also in animals (Nguyen et al 2020) . While positive or rewarding emotions may be experienced when the decision turns out to be a good one, untrustworthy ambiguous information triggers aversive emotions (FeldmanHall et al 2018) . To measure trustworthiness of information during decision-making we propose to add the aspect of "believing" to the concept of decisional anhedonia during decision-making under ambiguity.…”
Section: Introductionmentioning
confidence: 99%